Publish in the Journal of Dental Research by mapping active research areas - Mohammad Hossein Nekoofar; Ali Gazni (Tehran University of Medical Sciences, 2023)
Background and Aims: Journal of Dental Research is among the dentistry journal with the highest impact factor. This study aimed to map the most important topics for journal editors and readers. Materials and Methods: The world's active research topics in the field of dentistry related to the Journal of Dental Research in the last 5 years were extracted from SciMapper's SciTrends. Also, we clustered the most cited papers in that journal to show the most important research topics for the journal editors and readers. Results: We identified and mapped 11 active international research areas in the field of dentistry and related to this journal. Among 146 faculty members of the school of dentistry, 12 had at least one article related to the most active research areas in the journal. In this regard, they had similar articles elated to the 7 clusters out of 13, but their articles are mainly related to the clusters 7 and 19. Among the investigated faculty members, nine had directly collaborated with 21 authors of the mapped clusters. Moreover, 12 faculty members could also connect to the 126 authors with articles in that journal through their scientific collaborators. Conclusion: One way to publish in a top international journal is to know the most active and interesting research areas for the journal editors and readers. About 8% of the school of dentistry faculty members at Tehran University of Medical Sciences had some research related to the Journal of Dental Research.